Factors Affecting Farmers' Decision in Using Pesticides: A Case of Chili-Based Agribusiness in Central Java, Indonesia - Mariyono, Joko (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2013)
Chili-base agribusiness is profit-promising in Indonesia, but it risky, and so farmers apply pesticides on chili field to deal with the risk. There is a wide variation on level of pesticide use across farmers and across the locations within the province. This paper analyzes factors that determine level of pesticide use in chili farming in Central Java, Indonesia. Using a theory of subjective economic threshold (ET), the factors affecting pesticides use decision of farmers were examined. Data for this study were compiled from a survey conducted in Central Java in 2008, which involved 160 chili growing farm households from three districts. Tobit regression model was used. The results show that factors leading to higher doses of application of pesticides were market price of chili, number of insect pests on the field as observed by farmers, non-hybrid variety of chili, and more frequency of spray in a season, cocktail method of pesticide spray, and production location. On the other hand, factors that reduce use of pesticides were increase in prices of pesticides, higher level of farmers' education and long years of farming experience, more number of diseases observed by farmers, and large acreage cultivated to chili.